Digitalization - Challenges for Human Resource Management (International Journal of Food and Nutritional Sciences, 2019)
The digital revolution has had a profound impact on modern businesses on a wide range offronts. All of an organization's internal and external procedures are immediately affected bydigitalization. Because of its critical importance to economies and societies, digitalization hasbeen underway for quite some time, nevertheless, the introduction of cutting-edge technologieslike big data analytics, blockchain technology, artificial intelligence, data mining, the Internetof Things, etc. has further accelerated it.